46th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics and Materials Conference 2005
DOI: 10.2514/6.2005-1920
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Randomness in Mechanical Properties of Carbon Nanotubes Through Atomistic Simulation

Abstract: Carbon nanotubes (CNTs) have generated intense interest in the research community owing in part to their extraordinary mechanical properties. Nevertheless, experiment data on CNT mechanical properties exhibit significant variability. At least a part of these variabilities is due to the randomly occurring and randomly evolving defects on these small-scale structures. It is well docume nted that defects such as vacancies, pentagons, heptagons, Stone-Wales (SW) pairs, heterogeneous atoms etc. are commonly present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Benchmarking studies investigating the tensile and fracture behaviour of such simulations have already been reported in the literature [16,10,33,34]. It has been found that there is no discernible yield point and fracture of SWNTs is always catastrophic, although a crack-length dependence on fracture resistance has been found.…”
Section: Incorporating Random Stone-wales Defects In Swnt Mechanicsmentioning
confidence: 99%
“…Benchmarking studies investigating the tensile and fracture behaviour of such simulations have already been reported in the literature [16,10,33,34]. It has been found that there is no discernible yield point and fracture of SWNTs is always catastrophic, although a crack-length dependence on fracture resistance has been found.…”
Section: Incorporating Random Stone-wales Defects In Swnt Mechanicsmentioning
confidence: 99%
“…Defects can also be introduced by mechanical loading [31] and electron irradiation [37]. These defects have been found to have significant influence on CNT mechanical properties [42,43]. It is reasonable to assume that such defects could initiate brittle fracture in CNTs under appropriate conditions.…”
Section: Introductionmentioning
confidence: 99%